Conquistador : Hernán Cortés, King Montezuma, and the last stand of the Aztecs - Levy, Buddy, 1960- (Bantam Books, 2008)
In 1519, Hernán Cortés arrived on the shores of Mexico with a roughshod crew of adventurers and the intent to expand the Spanish empire. Along the way, this brash and roguish conquistador schemed to convert the native inhabitants to Catholicism and carry off a fortune in gold. In Tenochtitlán, the City of Dreams, Cortés met his Aztec counterpart, Montezuma: king, divinity, ruler of a complex and sophisticated civilization with fifteen million people, and commander of the most powerful military machine in the Americas. Yet in less than two years, Cortés defeated the entire Aztec nation in one of the most astonishing military campaigns ever waged.--From publisher description.